Diiron Azadithiolates as Models for the [FeFe]-Hydrogenase Active Site and Paradigm for the Role of the Second Coordination Sphere - Rauchfuss, Thomas B. (Acc Chem Res, 2015)
The [FeFe] hydrogenases (H(2)ases) catalyze the redox reaction that interconverts protons and H(2). This area of biocatalysis has attracted attention because the metal-based chemistry is unusual, and the reactions have practical implications. The active site consists of a [4Fe–4S] cluster bridged to a [Fe(2)(μ-dithiolate)(CN)(2)(CO)(3)](z) center (z = 1− and 2−). The dithiolate cofactor is [HN(CH(2)S)(2)](2−), called the azadithiolate ([adt(H)](2−)). Although many derivatives of Fe(2)(SR)(2)(CO)(6–)(x)L(x) are electrocatalysts for the hydrogen evolution reaction (HER), most operate by slow nonbiomimetic pathways. Biomimetic hydrogenogenesis is thought to involve intermediates, wherein the hydride substrate is adjacent to the amine of the adt(H), being bonded to only one Fe center. Formation of terminal hydride complexes is favored when the diiron carbonyl models contain azadithiolate. Although unstable in the free state, the adt cofactor is stable once it is affixed to the Fe(2) center. It can be prepared by alkylation of Fe(2)(SH)(2)(CO)(6) with formaldehyde in the presence of ammonia (to give adt(H) derivatives) or amines (to give adt(R) derivatives). Weak acids protonate Fe(2)(adt(R))(CO)(2)(PR(3))(4) to give terminal hydrido (term-H) complexes. In contrast, protonation of the related 1,3-propanedithiolate (pdt(2−)) complexes Fe(2)(pdt)(CO)(2)(PR(3))(4) requires strong acids. The amine in the azadithiolate is a kinetically fast base, relaying protons to and from the iron, which is a kinetically slow base. The crystal structure of the doubly protonated model [(term-H)Fe(2)(Hadt(H))(CO)(2)(dppv)(2)](2+) confirms the presence of both ammonium and terminal hydrido centers, which interact through a dihydrogen bond (dppv = cis-C(2)H(2)(PPh(2))(2)). DFT calculations indicate that this H---H interaction is sensitive to the counterions and is strengthened upon reduction of the diiron center. For the monoprotonated models, the hydride [(term-H)Fe(2)(adt(H))(CO)(2)(dppv)(2)](+) exists in equilibrium with the ammonium tautomer [Fe(2)(Hadt(H))(CO)(2)(dppv)(2)](+). Both [(term-H)Fe(2)(Hadt(H))(CO)(2)(dppv)(2)](2+) and [(term-H)Fe(2)(adt(H))(CO)(2)(dppv)(2)](+) are highly active electrocatalysts for HER. Catalysis is initiated by reduction of the diferrous center, which induces coupling of the protic ammonium center and the hydride ligand. In contrast, the propanedithiolate [(term-H)Fe(2)(pdt)(CO)(2)(dppv)(2)](+) is a poor electrocatalyst for HER. Oxidation of H(2) has been demonstrated, starting with models for the oxidized state (“H(ox)”), for example, [Fe(2)(adt(H))-(CO)(3)(dppv)(PMe(3))](+). Featuring a distorted Fe(II)Fe(I) center, this H(ox) model reacts slowly with high pressures of H(2) to give [(μ-H)Fe(2)(adt(H))(CO)(3)(dppv)(PMe(3))](+). Highlighting the role of the proton relay, the propanedithiolate [Fe(2)(pdt)-(CO)(3)(dppv)(PMe(3))](+) is unreactive toward H(2). The H(ox)-model + H(2) reaction is accelerated in the presence of ferrocenium salts, which simulate the role of the attached [4Fe–4S] cluster. The redox-complemented complex [Fe(2)(adt(Bn))(CO)(3)(dppv)-(FcP*)](n)(+) catalyzes both proton reduction and hydrogen oxidation (FcP* = (C(5)Me(5))Fe(C(5)Me(4)CH(2)PEt(2))).